1993
DOI: 10.1177/0148607193017003243
|View full text |Cite
|
Sign up to set email alerts
|

Aspirating Gastric Residuals Causes Occlusion of Small‐Bore Feeding Tubes

Abstract: A frequent mechanical problem encountered with small-bore feeding tubes is lumenal obstruction of the tube. A number of studies have described methods to prevent tube occlusion and restore patency once the tube becomes occluded. It has been observed that most intact protein formulas will clot when acidified to a pH of less than 5.0. This study evaluated the question of whether gastric feeding tubes occlude more frequently when they are used for checking gastric residuals by aspirating acidic gastric juices int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 14 publications
0
36
0
2
Order By: Relevance
“…16 Another study, 17 examining small bore feeding tube occlusion after residual checks, found no impact on the incidence of aspiration pneumonia when comparing groups that had residuals checked every 4 hours to those who had no residual checks done. 17 Mentec et al used the term upper digestive intolerance to study the effect of elevated gastric residuals on aspiration pneumonia rates. 18 Upper digestive intolerance was defined as one of the following: vomiting, the presence of 2 consecutive GRVs between 150 and 500 cc, or 1 GRV more than 500 cc.…”
Section: Gastric Residual Volumes As a Predictor Of Vomiting Or Aspirmentioning
confidence: 99%
“…16 Another study, 17 examining small bore feeding tube occlusion after residual checks, found no impact on the incidence of aspiration pneumonia when comparing groups that had residuals checked every 4 hours to those who had no residual checks done. 17 Mentec et al used the term upper digestive intolerance to study the effect of elevated gastric residuals on aspiration pneumonia rates. 18 Upper digestive intolerance was defined as one of the following: vomiting, the presence of 2 consecutive GRVs between 150 and 500 cc, or 1 GRV more than 500 cc.…”
Section: Gastric Residual Volumes As a Predictor Of Vomiting Or Aspirmentioning
confidence: 99%
“…The frequency of obstruction increases 10-fold when residuals are checked [15]. After initial monitoring of residuals for the first 4 h (every 2 h), residual checks ordinarily are not necessary, particularly if the patient does not display any physical or radiologic signs suggesting delayed gastric emptying (bloating, regurgitation, large gastric bubble, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it may be difficult to obtain accurate residuals from tubes smaller than 10 Fr because the lumen collapses on aspiration. Thus, in tubes 10 Fr or smaller, residuals may not be worth measuring [13,15]. Flushing with 30 ml of saline or water every 4 to 6 h, as well as before and after any residual check or instillation of medication, may aid in maintaining tube patency [13].…”
Section: Discussionmentioning
confidence: 99%
“…Small tube diameter and routine check of gastric residuals increase this risk [29] but they are supposed to be due to interactions between nutritional formulas and medications [3]. Routine water flushing after feedings can prevent tube occlusion.…”
Section: Tube Cloggingmentioning
confidence: 99%